HUBUNGAN LATAR BELAKANG PENDIDIKAN PENGASUH DAN KEMAMPUAN PENGUASAAN ALAT PERMAINAN EDUKATIF DENGAN KEAKTIFAN BERMAIN ANAK BALITA DI KECAMATAN NGALIYAN KOTA SEMARANG - Mujiyono Mujiyono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2007)
Every baby "when theyplay needs a baby sister who has a good education background. The aim of this research is 10kJK.,w the relationship between the education bacground with the activities babies play. Non experimem research has done at sub district of Ngalian in Semarang Regency, by using correlation design anJ involved 70 nursemaid whose nursing 1-2 year old children at Sub district ofNgal ian in the Semarang Regency. This research is using descrieoon prosentation metbode. The research purposes say that the educa tion background influence part of (57%) the senior high school graduated. The exclution that have influence the higher education background will influence the babies playing.